2021
DOI: 10.1111/cen.14438
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of radiofrequency ablation and microwave ablation for benign thyroid nodules: A systematic review and meta‐analysis

Abstract: Purpose To compare the effectiveness and safety of radiofrequency ablation (RFA) and microwave ablation (MWA) for the treatment of benign thyroid nodules (BTNs). Methods PubMed, Embase and Cochrane databases were searched up to September 11, 2020. Volume reduction rate (VRR), symptomatic and cosmetic scores analysed by standardized mean difference (SMD), and complications analysed by risk difference (RD) were performed to evaluate the efficacy and safety of RFA and MWA for treating BTNs. Results Five eligible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 41 publications
5
18
0
Order By: Relevance
“…To our knowledge, there has been no report of the results of MWA or BTNs after >2 years of follow-up. Articles comparing the efficacy of RFA and MWA after a 1 year follow-up period reported that the results were similar [46,55].…”
Section: Ta Modalitiesmentioning
confidence: 99%
“…To our knowledge, there has been no report of the results of MWA or BTNs after >2 years of follow-up. Articles comparing the efficacy of RFA and MWA after a 1 year follow-up period reported that the results were similar [46,55].…”
Section: Ta Modalitiesmentioning
confidence: 99%
“…In the ablation of thyroid nodules, some literatures have compared RFA with LA and found that RFA is faster than LA which led to a conclusion that regeneration is less but requires higher energy (43,44). There is also literature comparing RFA and MWA, suggesting that RFA may have a better long-term effect in reducing nodule volume (45).…”
Section: Discussionmentioning
confidence: 99%
“…And VRR after MWA was 53.9%, 74.9% and 80.0%, respectively. Significant decreased symptomatic and cosmetic scores were found after 6 and 12 months for both RFA and MWA (6). Besides, another study demonstrated that the incidence of hoarseness, hypothyroidism and postoperative pain were lower after thermal ablation compared to conventional thyroidectomy (9).…”
Section: Introductionmentioning
confidence: 96%
“…Thus, minimally invasive treatments are needed for benign PCTNs. Ultrasound(US)-guided thermal ablation, including radiofrequency ablation(RFA) and microwave ablation(MWA), was proved to be an effective substitute for surgery, which can decrease the nodule size significantly and simultaneously preserve the thyroid function and minimize complications (4)(5)(6)(7)(8). A metaanalysis showed that volume reduction rate (VRR) at 3, 6, and 12 months was 56.0%, 80.8% and 86.2% after RFA.…”
Section: Introductionmentioning
confidence: 99%